Damage recovery and low‐damage etching of ITO in H2/CO plasma: Effects of hydrogen or oxygen. Issue 9 (24th April 2019) - Hirata, Akiko; Fukasawa, Masanaga; Kugimiya, Katsuhisa; Karahashi, Kazuhiro; Hamaguchi, Satoshi; Nagaoka, Kojiro
Abstract: Hydrogen‐containing plasma etching of tin‐doped indium oxide (ITO) causes surface reduction damage induced by the plasma itself. Damage recovery by using O‐containing plasma and low‐damage etching in plasma with hydrogen and oxygen were investigated. While recovery was possible with O2 plasma after H‐containing plasma exposure, O 2 plasma caused excess oxidation of the ITO surface, which can degrade device properties. Simultaneous injection of hydrogen and oxygen recovered the reduced ITO to its initial state. The etching performance was also investigated; low‐damage etching was achieved with hydrogen and oxygen‐mixed plasma by controlling the balance between surface reduction and oxidation. Abstract : Hydrogen‐containing plasma etching of tindoped indium oxide (ITO) causes surface reduction damage induced by the plasma itself. Damage recovery by using O‐containing plasma and low‐damage etching in plasma with hydrogen and oxygen were investigated. While recovery was possible with O2 plasma after H‐containing plasma exposure, O2 plasma caused excess oxidation of the ITO surface, which can degrade device properties. Simultaneous injection of hydrogen and oxygen recovered the reduced ITO to its initial state.